Transition from Copper to Fiber Broadband: The Role of Connection Speed and Switching Costs - Lukasz Grzybowski; Maude Hasbi; Julienne Liang (Center for Economic Studies and ifo Institute (CESifo), 2018)
We estimated a mixed logit model using data on the broadband technologies chosen by 94,388 subscribers of a single European broadband operator on a monthly basis between January and December 2014. We found that consumers have similar valuation of DSL connection speeds in the range between 1 and 8 Mbps. Moreover, in January 2014, the valuation of FttH connections with a speed of 100 Mbps was not much higher than of DSL connections with a speed of 1 to 8 Mbps, but it has increased quickly over time. The small initial difference in the valuation of DSL and FttH connections may be because consumers' basic Internet requirements such as browsing, emailing, reading news, shopping, and even watching videos online could be satisfied with a connection speed below 8 Mbps. We also found that consumers face significant switching costs when changing broadband tariff plans, which are substantially higher when switching from DSL to FttH technology. According to counterfactual simulations based on our model, switching costs between technologies are the main factor which slows down consumer transition from DSL to FttH.
Keywords: L43; L50; L96; 330; FttH; DSL; connection speed; switching costs